(untitled) - Mehta, Dileep R. (Malden, MA, 2004)
International Bank Management provides current, integrated coverage of international banking issues, including foreign exchange markets, derivatives, country risk analysis, asset-liability management, and banking strategies. Mehta & Fung utilize a variety of analytical frameworks to explain important decision-making processes and illustrate their applications through real-world examples. Learning objectives and end-of-chapter review questions reinforce key themes and concepts. A focus on the increasing globalization of financial markets in this text enables students to obtain the comprehensive, international perspective essential for a successful career in banking.
Keywords: Banks and banking, International,Ngân hàng và hoạt động ngân hàng, Quốc tế; Management,Quản lý